Land Acquisition Act 1960: the rights of the landowner in respect of his property / A. Rahman Mohd Nasir … [et al.] - Mohd Nasir, A. Rahman; Mohd Rassul, Nora Affizza; Rahtimin, Siti Adora; Hashim, Rohaizon; Abd Mutalib, Nor-Ain (Faculty of Law, 2009)
This research project is a research to review the land acquisition in Malaysia which include the process of land acquisition involving the procedure to make application to acquire land; the procedure to make objection on land acquisition; and the procedure to make payment of the compensation. It study the guideline for the determination of the compensation and how the valuation should be made to answer the question of what makes compensation adequate. This paper stress on the rights of the landowner in land acquisition where they do have some rights provided by the law. This research is set out to reviews the process of the land acquisition in Malaysia, the valuation for compensation and the right of the landowners in the land acquisition as the whole. This paper had successfully examine the implementation and the enforcement of law relating to land acquisition in Malaysia. It had investigate the strength and weakness of land acquisition law in Malaysia on how the law provides justice and protect the rights of the landowner in land acquisition. Other than that, this research had discover the adequacy of the land acquisition law that being practice in Malaysia where it had figure out that the existing law needs some improvements and advancements for a betterment. As conclusion, the law had provide wide power to the land administrator to acquire land. The law itself is adequate to provide justice to the parties in land acquisition, however the practice did not achieve the objectives of the Act.